Effects of intermittent suckling on body composition of Iberian piglets weaned at 35 days of age. (24th February 2014) - Castellano, R.; Aguinaga, M. A.; Nieto, R.; Aguilera, J. F.; Haro, A.; Seiquer, I.
Abstract : Piglet body composition at weaning could be a determinant for pig's viability and may be influenced by factors such as the nutritional management followed during suckling. An experiment was conducted to study whether intermittent suckling (IS) affects body composition at weaning and nutrient and energy retention during a 34-day lactation period in Iberian piglets. Litters were subjected to conventional suckling (CS) or IS ( n =10 litters of six piglets per treatment) in two trials. All piglets had ad libitum access to creep feed from day 15 onwards. In IS, piglets were progressively separated from the sow for 6, 8 and 10 h daily during the last week of lactation, whereas in CS piglets had continuous access to their dams. Creep feed intake in litters and BW development of individual piglets were measured throughout the 34-day lactation. Within each litter, both at birth and at weaning (day 35), one piglet was used to assess nutrient retention and body composition by the comparative slaughter approach. During days 29 to 35 of the experiment, daily creep feed intake was greater in IS piglets (IS 124, CS 67 g/piglet, P =0.040), and average daily gain differed significantly between groups (IS 190, CS 150 g/day, P =0.010). BW at weaning was higher in the IS than in the CS piglets (IS 8.19, CS 7.48 kg, P =0.011). Empty-body fat and energy content at weaning were higher in the IS compared with CS litters, as well as fat content in the carcass ( P =0.04). The IS treatment did not affect empty-body protein deposition, but significantly increased daily retention of fat, energy, ash and calcium, compared with CS litters ( P <0.05). Thus, IS in Iberian piglets seems to enhance feed intake, growth rate and retention of some body components, which may contribute to a higher body fat content at weaning and facilitate the weaning process.